VERTICAL DISTRIBUTIONS OF TEMPERATURE, SALINITY AND GEOSTROPHIC FLOW ALONG 45°W IN THE SOUTHERN OCEAN (EXTENDED ABSTRACT) (15th Symposium on Polar Biology) - ナガノブ, ミキオ; ヒサナガ, ミツル; シマヅ, ヤスヒコ; NAGANOBU, Mikio; HISANAGA, Mitsuru; SHIMADZU, Yasuhiko (National Institute of Polar Research, 1994)
P(論文) departmental bulletin paper